Analisis Proses Manajemen Kualitas Perangkat Lunak Pada Sistem Informasi Universitas Al Azhar Indonesia: Pada Sistem Informasi Universitas Al Azhar Indonesia - Umar; Prayogi, Muhamad Nur; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2026)
Along with the development of technology, the need for software in all fields is increasing every year. Software is needed in all sectors to help running business processes. The success or failure of a software that is built can be seen based on whether or not the software works according to the running business processes. In the scientific concept that exists in software engineering, the success of software is seen from various aspects of the suitability of the product produced against existing needs. The success of the software can also be seen from the management process and the quality of the software. But the facts found in this study, the management process and software quality are not given proper attention. Based on the results of a literature study, software quality is not only seen based on the suitability of the product produced but also seen based on quality assurance during the software development process. Based on this observation, it was found that the monitoring process for the software development process along with the software quality factors in each software built still needs to be improved. Therefore it is necessary to identify the components of quality assurance of existing devices to ensure the quality management process can run well and readiness to build a quality software.